METHODOLOGY FOR FORMING CONSTRUCTION SKILLS IN STUDENTS OF THE GROUP FOR PREPARING FUTURE TEACHERS FOR SCHOOL (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This research paper examines a comprehensive methodology for developing construction skills in pre-service teachers. Recognizing the importance of hands-on experience and hands-on learning in developing these skills, the methodology combines theoretical knowledge with experiential activities to enhance students’ understanding and proficiency in construction-related tasks. Emphasizing active learning, collaborative projects, and reflective practices, this methodology aims to equip pre-service teachers with the necessary competencies to effectively teach and facilitate construction skills in their students.